2022
DOI: 10.3390/rs14153788
|View full text |Cite
|
Sign up to set email alerts
|

First Ever Observations of Mineral Dust in Wintertime over Warsaw, Poland

Abstract: The long-range transport of desert dust over the area of the temperate climate zone is associated with the influx of hot air masses due to the location of the sources of this aerosol in the tropical climate zone. Between 24–26 February 2021, such an aerosol outbreak took place and reached Central Europe. The mean temperature of +11.7 °C was recorded during the event. A comparison of this value to the 20-year (2000–2020) average February temperature for Warsaw (−0.2 °C) indicates the uniqueness of the meteorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…Other research groups have reported aerosol/dust optical and microphysical parameters, particularly BSC and (B)AE, with value ranges similar to the ones presented above, regarding the same dust episode [59,121].…”
Section: Lidar Aerosol/dust Retrievals and Radiosonde Datasupporting
confidence: 81%
See 2 more Smart Citations
“…Other research groups have reported aerosol/dust optical and microphysical parameters, particularly BSC and (B)AE, with value ranges similar to the ones presented above, regarding the same dust episode [59,121].…”
Section: Lidar Aerosol/dust Retrievals and Radiosonde Datasupporting
confidence: 81%
“…This seriously impacted the air quality and seasonal climate conditions in the affected regions. These dust events were the subject of research interest and study, as reflected in the specialized scientific literature [59,[119][120][121]. Here, we present the results of experimental and model studies on the second of the two dust episodes noted.…”
Section: Dust Episode Descriptionmentioning
confidence: 92%
See 1 more Smart Citation
“…The above-discussed characteristic parameters and environmental conditions concerning the aerosol field over Sofia on 26 February 2021 reveal a mixed aerosol situation with MA and SD making up the coarse-particle-rich aerosol component. Let us note that 25 and 26 February 2021 were days of a dust flow drop in the middle of a period of a massive transport to Europe of Saharan dust (Hoshyaripour, 2021;Szczepanik et al, 2022;Peshev et al, 2023), whose influence on the aerosol situation and especially on the concentration of PM10 through sedimentation was noticeable.…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, where a humid climate dominates, water-induced soil erosion is the main form of erosion, which poses a serious environmental concern in many European countries [ 6 ]. Furthermore, soil erosion by wind and dust storms is one of the challenges in European countries [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%